HPV and Penile Cancer: Epidemiology, Risk Factors, and Clinical Insights - Gowtam Mannam; Justin W. Miller; Jeffrey S. Johnson; Keerthi Gullapalli; Adnan Fazili; Philippe E. Spiess; Jad Chahoud (Pathogens, 2024)
Penile cancer (PC) is a rare malignancy predominantly of squamous cell origin. Approximately 40% of penile tumors are associated with human papillomavirus (HPV) infection. Diagnosing PC remains challenging due to its rarity and variety of clinical presentations. Furthermore, the impact of HPV on the tumor immune microenvironment complicates clinical management, although recent advancements in immune checkpoint inhibitors (ICIs) have shown some efficacy in treating HPV-associated PC. Ongoing research efforts aim to develop oncologic treatments that target HPV-induced cellular modifications. Additionally, novel therapeutic vaccines and adoptive T-cell therapies targeting HPV oncoproteins represent emerging treatment modalities. Our review highlights the complex interplay between HPV and penile carcinogenesis, emphasizing its epidemiology, etiology, clinicopathological characteristics, and potential therapeutic implications.